Management of complex benign post-tracheostomy tracheal stenosis with bronchoscopic insertion of silicon tracheal stents, in patients with failed or contraindicated surgical reconstruction of trachea - Tsakiridis, Kosmas (Pioneer Bioscience Publishing Company, 2012)
Tracheal stenosis is a potentially life-threatening condition. Tracheostomy and endotracheal intubation remain the commonest causes of benign stenosis, despite improvements in design and management of tubes. Post-tracheostomy stenosis is more frequently encountered due to earlier performance of tracheostomy in the intensive care units, while the incidence of post-intubation stenosis has decreased with application of high-volume, low-pressure cuffs. In symptomatic benign tracheal stenosis the gold standard is surgical reconstruction (often after interventional bronchoscopy). Stenting is reserved for symptomatic tracheal narrowing deemed inoperable, due to local or general reasons: long strictures, inflammation, poor respiratory, cardiac or neurological status. When stenting is decided, silicone stent insertion is considered the treatment of choice in the presence of inflammation and/or when removal is desirable. We inserted tracheal silicone stents (Dumon) under general anaesthesia through rigid bronchoscopy in two patients with benign post-tracheostomy stenosis: a 39-year old woman with failed initial operation, and continuous relapses with proliferation after multiple bronchscopic interventions, and a 20-year old man in a poor neurological status, with a long tracheal stricture involving the subglottic larynx (lower posterior part), and inflamed tracheostomy site tissues (positive for methicillin resistant staphylococcus aureus). The airway was immediately re-establish, without complications. At 15- and 10-month follow-up (respectively) there was no stent migration, luminal patency was maintained without: adjacent structure erosion, secretion adherence inside the stents, granulation at the ends. Tracheostomy tissue inflammation was resolved (2(nd) patient), new infection was not noted. The patients maintain good respiratory function and will be evaluated for scheduled stent removal. Silicone stents are removable, resistant to microbial colonization and are associated with minimal granulation. In benign post-tracheostomy stenosis silicone stenting appeared safe and effective in re-stenosis after surgery and multiple bronchoscopic interventions, and in long stenosis, involving the lower posterior subglottic larynx in the presence on inflammation and poor neurological status.